Effect of milling and mixing of Ba₀.₇₀Sr₀.₃₀Tio₃ electroceramics / Saidatulakmar Shamsuddin, Prof Madya Dr Ahmad Fauzi Mohd Noor and Prof Dr Zainal Arifin Ahmad - Shamsuddin, Saidatulakmar; Fauzi Mohd Noor, Ahmad (Prof Madya Dr); Ahmad, Zainal Arifin (Prof Dr) (2005)
The effects of milling and mixing of BaC0₃, SrC0₃ and Ti0₂ on the dielectric constant and microstructures properties of Ba₀.₇₀Sr₀.₃₀Tio₃ electroceramics were investigated using conventional ball milling method. The set A of samples came from the process of mixing and milling of barium carbonate, strontium carbonate and titanium (IV) dioxide. The set B came from the process of milling barium carbonate with titanium (IV) dioxide and milling of strontium carbonate with titanium (IV) dioxide followed by the mixing process of barium carbonate with titanium (IV) dioxide and strontium carbonate with titanium (IV) dioxide. Each set were milled with zirconia balls at ball to powder ratio of 3:2 inside a polyethylene container. The rotation milling speed is 75 rpm for the duration of 12 hours, 18 hours and 24 hours. Single phase Ba₀.₇₀Sr₀.₃₀Tio₃ by solid state reaction was successfully formed, revealed by the x-ray diffraction data at room temperature, at the calcinations temperature of 1150°C. Sample with three type of thermal treatment at 1250, 1300 and 1350°C have been manufactured and analyzed. The microstructures of Ba₀.₇₀Sr₀.₃₀Tio₃ were studied using scanning electron micrograph. The grain size increases with increased of temperature and subsequently leading to formation of large grains at higher sintering temperature. The dielectric constant was determined from the calculation of capacitance measured using Philips PM6303 RCL meter. It was found that the samples from set A produced better properties compared to set B. It was concluded that the dielectric constant was linked to the uniformity of the grain size.